Karakterisasi Simplisia, Ekstrak dan Spektra Infra Merah Senyawa Analgesik Daun Dadap Serep (Erythrina Subumbrans) Dari Kabupaten Magelang - Arief Kusuma Wardani; Perdana Priya Haresmita; Tesia Aisyah Rahmania; Missya Putri Kurnia Pradani (Fakultas Farmasi Universitas Setia Budi, 2025)
Medicinal raw materials from agricultural products or groups of wild plants cannot be guaranteed; their chemical content is always constant due to variations in seedlings, body location, climate, or raw material conditions (age and harvest method). The content of the chemical compounds responsible for the biological response must have a chemical specification, i.e., information about the composition of both type and content. Standardization was carried out on specific parameters, including organoleptics, yield, the content of drying losses, water-soluble extract content, ethanol-soluble extract content, and chromatogram patterns. Non-specific parameters of the extract included water content, total ash content of powder and extract. The method of determination is carried out in accordance with the procedures established by Farmakope Herbal Indonesia (FHI 2017). Profiling has been done using infrared spectroscopy. Specific parameters showed that the organoleptic was a semisolid form with a dark green color, a distintive smell of dadap serep leaf extract, bitter sweetness, a yield of 7,63%, a drying loss of 7,51%, a water-soluble extract content of 4,86%, a level of ethanol-solubility extract content of 33,47%, and chromatogram patterns that were typical. Non-specific parameters indicate that the water content is 1,11%, acid-insoluble ash powder content 5,050 ± 0,036%; extract 0,986% and total ash powder content is 8,671 ± 0,303%; extract 4,123%. The results of parameter simplicia as well as ethanol extracts of leaves of Dadap Serep obtainable from the Magelang in accordance with the specifications in FHI 2017 and the spectroscopic photometer profile showing the typical pattern of extract and simplisia leaves.